2017
DOI: 10.1007/s13595-017-0673-7
|View full text |Cite
|
Sign up to set email alerts
|

Local-scale diversity and adaptation along elevational gradients assessed by reciprocal transplant experiments: lack of local adaptation in silver fir populations

Abstract: & Key message Silver fir transplantations along elevational gradients revealed a high diversity but no local adaptation. Populations displayed similar abilities to adapt to new environments including those due to climate change. & Context The sustainability of forest stands depends on the ability of species and communities to adapt by combining plasticity and genetic evolution. Although well-documented at the scale of species distributions, the variability and adaptation of forest tree genetic resources are le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
1
26
3
Order By: Relevance
“…2 should be interpreted only within the context for this experiment. As an example, a recent transplantation experiment of silver fir, also from the French Mediterranean Alps, found that much lower proportion of the trait variance was explained by family than this study (Latreille & Pichot, 2017). Heterogeneity was also introduced via the orientation of the greenhouse: greenhouse 1 was exposed to more wind, which can have a major effect on the temperature of the greenhouse.…”
Section: Discussioncontrasting
confidence: 70%
“…2 should be interpreted only within the context for this experiment. As an example, a recent transplantation experiment of silver fir, also from the French Mediterranean Alps, found that much lower proportion of the trait variance was explained by family than this study (Latreille & Pichot, 2017). Heterogeneity was also introduced via the orientation of the greenhouse: greenhouse 1 was exposed to more wind, which can have a major effect on the temperature of the greenhouse.…”
Section: Discussioncontrasting
confidence: 70%
“…However variance analysis did not confirm significant environmental differentiation, confirming the low percentage of variation explained by the environmental effect (4.23%) which may be related to the relatively restricted area occupied by testing sites. However, similar studies on half-sib families collected from 15 French silver fir provenances provided opposite results, indicating that most of the phenotypic variability was attributed to the environmental factors [59]. The reverse trend obtained in the presented studies may be related to slight variation in the altitude of testing sites and populations (from 380 to 670 and from 314 to 688 m, respectively).…”
Section: Discussioncontrasting
confidence: 46%
“…Data on perennial plants, and on trees in particular, suggest that this may be a general phenomenon, that can be readily observed at the phenotypic level (Yeaman and Jarvis 2006;Brousseau et al 2013;VizcaĂ­no-Palomar et al 2014;Lind et al 2017) (but see Latreille & Pichot (2017) for a case of complete lack of microgeographical adaptation) . At the molecular level, association between alleles (or genotypes) and habitats has been detected in a variety of cases (Cobb et al 1994;Mitton et al 1998;Kelly et al 2003;Jump et al 2006;Pluess and Weber 2012;Audigeos et al 2013;CsillĂ©ry et al 2014;Brousseau et al 2015;Eckert et al 2015;Lind et al 2017), which led us to a reconsideration of the adaptive role of intra-specific and intra-populational variation (Scotti et al 2016) .…”
Section: Introductionmentioning
confidence: 99%